G304 Delphi consensus process for the uk guidelines for management and surveillance of tuberous sclerosis complex. (12th March 2018) - Amin, S; Kingswood, C; O'Callaghan, F
Abstract : Background: Tuberous Sclerosis Complex (TSC) is a multi-systemic genetic disease. The severity of TSC can vary among affected individuals. Complications of TSC can be life threatening, with significant impact on patients' quality of life. Management may vary dependent on treating physician, local and national policies and funding. There are no current UK guidelines. We conducted a Delphi consensus process to gain consensus on the management of patients with TSC in the UK. Methods: We invited 86 clinicians and researchers to complete an online survey in two rounds. All the people surveyed were based in the UK. Clinicians were identified through the regional TSC clinics, and researchers were identified through publications. In round one, 55 questions were asked. They were related to surveillance and management recommendations for those newly diagnosed, suspected, or already diagnosed with TSC. In round two, 18 questions were asked to obtain consensus on the outstanding points that had been contentious in round one or needed clarification. Results: 51 (60%) responded to the survey. Three rounds were required to achieve consensus. The responders were neurologists, nephrologists, psychiatrists, psychologists, oncologists, general paediatricians, dermatologists, urologists, radiologists, geneticists, neurosurgeons, pulmonologists and neurodisability clinicians. A priori consensus was defined as 70% agreement among participants. The Delphi process is now complete and the consensus management recommendations will be presented at conference. Conclusions: This new UK guideline for the management and surveillance of TSC patients provides a realistic, cost effective, an evidence-based approach for best clinical care delivered for individuals with tuberous sclerosis complex in the UK.